New polyurea MWCNTs nanocomposite films with enhanced mechanical properties. Issue 28 (20th March 2017) - Toader, Gabriela; Rusen, Edina; Teodorescu, Mircea; Diacon, Aurel; Stanescu, Paul O.; Damian, Celina; Rotariu, Traian; Rotariu, Adrian
ABSTRACT: Polyurea nanocomposites represent a promising option in the development of advanced materials for applications that require high mechanical resistance. This article describes an optimized synthetic route for obtaining polyurea nanocomposites with enhanced mechanical properties by employing epoxy‐functionalized multiwalled carbon nanotubes (MWCNTs) as reinforcing agent. The experimental measurements revealed that these functionalized nanofillers have a positive effect on the properties of the composite only until they reach a certain concentration; therefore, the optimal composition was reported (the samples containing 0.2 weight % functionalized MWCNTs). The functionalization of the MWCNTs was confirmed through RAMAN, X‐ray photoelectron spectroscopy, scanning electron microscopy and thermogravimetric analysis, while the polyurea nanocomposites obtained have been characterized by thermal (differential scanning calorimetry and TGA) and mechanical (dynamic mechanical analysis and tensile tests) analyses. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45061. Abstract :